ANALISIS PROGRAM KERJA KEPALA SEKOLAH DALAM MENINGKATKAN KOMPOTENSI GURU DI SD INPRES KUANINO 3 KOTA KUPANG - ABNER HAKI, ABNER ABYATER HAKI; Tanggur, Fembrianus Sunario; Naitili , Cornelia Amanda (FKIP Universitas Citra Bangsa, 2025)
Abstract. This research examines the analysis of the principal's work program in increasing teacher professionalism at SD Inpres Kuanino 3, Kupang City. The aim of this research is to determine the role of the principal in order to improve teacher professionalism which includes six aspects, namely: the role of the principal as a leader, the role of the principal as a motivator, the role of the principal as a supervisor, the role of the principal as an innovator, the role of the principal as a manager and the role of the school principal as an educator. This research approach is qualitative with a descriptive format qualitative research type. Data collection techniques include observation, interviews and documentation. The results of the research show that: the implementation of the role of the school principal at SD Inpres Kuanino 3 Kupang City is going quite well. This means that the role of the school principal in order to increase teacher professionalism is very dominant. The forms, obstacles and strategies of school principals in improving teacher professionalism include the following: a) Improving teachers' pedagogical skills such as by participating in various activities in the form of seminars, workshops, teacher meetings and workshops. b) Lack of facilities and infrastructure owned by schools to improve teacher professionalism. c) Providing opportunities for teachers to take part in various training to improve their professionalism. Based on the results of this research, it can be concluded that the role of the principal as a leader at SD Inpres Kuanino 3 Kupang City holds training to improve and develop teachers' professional competence in the application of learning support components. Keywords: Work Program, Principal, Teacher Professionalism.